PREVALENCE OF HEALTH PROBLEMS AMONG MENOPAUSAL WOMEN AND ASSESSMENT OF THEIR QUALITY OF LIFE: A COMMUNITY-BASED STUDY IN WESTERN ODISHA - MONIKA SATPATHY* and CHANDRASHREE LENKA (The Journal of Research ANGRAU, 2020)
Menopause is a natural phenomenon in every of women’s health. The descriptive cum exploratoryresearch study was carried out in western Odisha among 330 rural, urban, and tribal women in theage group of 35-55 years, from April to September of 2018. Purposive sampling method was used toselect the respondents. The findings of the study revealed that the mean menopausal age was46.22±4.39 years. The most common symptoms reported by the women were irritability, physical andmental exhaustion (63%) and depression (56.96%). Hot flashes and night sweats were also found in61.51% of the respondents, whereas, joint pain and muscular pains were found in 66.06% of women.Urogenital problems like bladder problems and dryness of the vagina were found among 59.39% and35.45% respondents, respectively. However, a statistically significant association was found in theprevalence of menopausal symptoms and their degree of severity with menopausal status, and currentage of menopausal women in this study which ultimately affects the quality of life of the menopausalwomen.